¿Es rentable jugar en Primera División de fútbol? - Magaz-González, A. M.; Mallo-Fernández, F.; Fanjul-Suárez, J. L. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
The paper presents the first phase of a Spanish football study. The aim is to determine if it is profitable to play in 1ª D league for any professional team and if all clubs in 2ª A division should aspire to climb. Various results are compared in the selected population and also in two groups identified: equipment that have remained in 1ªD and "elevator teams". The economics and sports results are examined by exploratory data analysis. We identify factors that are influence in change and the teams are classified according to these factors. Finally the influence of promotion and relegation in these results is determined. It follows that the "Fear Management" doesn`t always lead to better classification and adds financial stress, "elevator equipment" that perform worse even playing in the same league and its economic and financial stability will most affect the rise and decline that continued the stay in a particular category. We conclude: not all clubs suit them military in 1ª, it would be to restructure and strengthen the 2ª A.